Intravoxel incoherent motion diffusion-weighted imaging as a quantitative tool for evaluating disease activity in patients with axial spondyloarthritis. Issue 6 (June 2022) - Guo, C.; Zheng, K.; Xie, Z.; Lu, X.; Wu, S.; Ye, Q.; He, Y.; Zhou, Q.; Sun, E.; Y. Zhao,
Abstract : AIM: To determine the correlations between four quantitative magnetic resonance imaging (MRI) parameters derived from intravoxel incoherent motion diffusion-weighted images (IVIM DWI) and the semi-quantitative Spondyloarthritis Research Consortium of Canada (SPARCC) score of the sacroiliac joint (SIJ) and five clinical activity indices in patients with axial spondyloarthritis (axSpA). AND METHODS: A total of 75 patients with axSpA and complete clinical activity indices and SIJ MRI were enrolled to this prospective study. Univariable and multivariable linear regression analyses were performed to evaluate correlations between MRI parameters and clinical activity indices after controlling for confounders. All data were further analysed using Pearson's correlation coefficients ( r ). RESULTS: Only pure diffusion coefficient (D) and incoherent perfusion related microcirculation (D∗) were found to be independently positively correlated with several clinical activity indices (all p< 0.05). Positive correlations were observed between D and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Bath Ankylosing Spondylitis Functional Index (BASFI), Patient Global Assessment (PGA), extent of influence of pain, with r of 0.605, 0.402, 0.319, and 0.485 (all p< 0.0125). D∗ correlated positively with BASDAI, BASFI, and PGA ( r =0.436, 0.356, 0.301, respectively; all p< 0.0125). CONCLUSION: D and D∗ derived from IVIM DWI could be associated with some disease activity indices in patients with axSpA; apparent diffusion coefficient (ADC) and SPARCC scores were not correlated with these indices. IVIM DWI may be a useful tool for the quantitative assessment of disease activity in patients with axSpA. Highlights: Parameters of IVIM DWI are correlated with disease activity of axSpA IVIM DWI may be a tool for observing disease activity of axSpA IVIM DWI is better than semi-quantitative score in assessing disease activity.